PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI (Studi Quasi Eksperimen Pada Siswa Kelas XI SMA Negeri 3 Tasikmalaya) - Rindiana Mariana; Raden Roro Suci Nurdianti; Kurniawan Kurniawan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The low learning outcomes of students in Economics at SMA Negeri 3 Tasikmalaya is a problem that needs to be addressed. Learning that is still dominated by lecture methods makes students less active and have difficulty understanding the material, which results in low learning outcomes. This study aims to determine the effect of the flipped classroom learning model on improving student learning outcomes. The method used is a quasi-experiment with a nonequivalent control group design. The sample consisted of class XI.F-12 as the experimental class and XI.F-7 as the control class, selected through purposive sampling. The instrument used was a multiple-choice test that had been validated and reliability-tested. Data analysis techniques employed the Wilcoxon and Mann-Whitney tests. The results of the study showed significant differences between students' learning outcomes before and after the treatment in the experimental class, as well as significant differences in learning outcomes between the experimental class and the control class after the treatment. The effect size test indicated that the flipped classroom model had a significant impact on improving learning outcomes. Thus, the implementation of this model was proven effective in improving students' learning outcomes in economics.